A case report. Tenosynovial giant cell tumour in the tendon of extensor digitorium longus. (June 2021) - Green, Richard; Protheroe, Derek
Highlights: (TSGCT) although rare are the sixth most common benign lesion in the foot, behind a ganglion cyst, plantar fibroma, epidermal inclusion cyst, lipoma and rheumatoid nodules. Advanced imaging and prompt referral allow for the most appropriate management plan to be commenced when suspecting a TSGCT. Intra-operative assessment and histopathology should be the gold standard in arriving at a final diagnosis of TSGCT in the foot. Abstract: Soft tissue lesions found within the foot and ankle can vary in their origin. Tenosynovial giant-cell tumours (TSGCT) are quoted as rare in their presentation yet also reported to be the sixth most common benign lesion in the foot. This article presents a case report following the patient journey suffering with a TSGCT of the fourth toe. From initial consultation, to further investigation with advanced imaging to a final decision on surgical excision following consideration of conservative management.